Vzaimosvjaz' polimorfizmov genov s razvitiem fizicheskih kachestv u sportsmenov (na materiale kon'kobezhnogo sporta) - Ilyutik, A.; Gilep, I. (Science in Olympic Sport, 2017)
The paper summarizes the results of the studies on the identification of the relationship between the polymorphisms in a number of genes with the manifestation of speed-strength qualities and endurance in speed skaters. The theoretical and experimental substantiation is presented for the algorithm of determining the sports specialization of athletes specializing in speed skating on the basis of the results of polymorphism analysis of the genes ACE, NOS3, BDKRB2, ACTN3, PPARG, and CYP17A1. The algorithm consists of determining both the polymorphism of individual genes and the combinations of gene polymorphisms, thus making it possible to estimate the number of alleles and genotypes associated with endurance and/or speed-strength qualities. The use of this algorithm enables identifying physical qualities, to the development of which there is the greatest genetic predisposition, and choosing on their basis a skating specialization of the athlete.Keywords: sports genetics, genetic testing of highly qualified athletes, genetic selection of young athletes, speed skaters, molecular genetic technologies.